2nd Symposium of Applied Science for Young Researchers: Proceedings - Fernandes, Florbela P. (Ed.) (2022)
This document presents the proceedings of the 2nd Symposium of Applied Science for Young Researchers - SASYR. This scientific event welcomed works by junior researchers on any research topic covered by the following three research centres: ADiT-lab (from IPVC, Instituto Politécnico de Viana do Castelo), 2Ai (from IPCA, Instituto Politécnico do Cávado e do Ave) and CeDRI (from IPB, Instituto Politécnico de Bragança). The main objective of SASYR is to provide a friendly and relaxed environment for young researchers to present their work, discuss recent results and develop new ideas. In this way, this event offered an opportunity for the ADiT-lab, 2Ai, and CeDRI research communities to gather synergies and promote collaborations, thus improving the quality of their research. The SASYR 2022 took place in a hybrid environment at Escola Superior de Tecnologia e Gestão of Instituto Politécnico de Viana do Castelo on the 22nd of June, 2022.